Analysis of a Possible Battery Chargertopology - Yvonne Flicker; Felix A. Himmelstoss (Communications - Scientific letters of the University of Zilina, 2013)
Battery chargers are very important, especially for handhelds and cars. In this paper a converter is analyzed which enables us to control the voltage across the battery for a high input voltage range. Using the converter as a battery charger, the load current has to be controlled. Consequently, a two-point controller can be used. Therefore, a draft of a two-point controller is given. In addition, the weighted state differential equations are linearized in order to use the possibilities of the linear control theory. A basic analysis of the charger topology is given, the losses are approximated, and some experimental results are presented.